القراءات المتواترة في كتاب روائع البيان في تفسير آيات الأحكام من القرآنلمؤلفه محمد علي الصابوني: The Mutawātir Readings in Rawā’i‘ Al-Bayān in The Exegesis of The Qur’anic Legal Verses By Muḥammad ‘Alī Al-Ṣābūnī - Gampang Dadiyono; Muhammad Galib; Muhsin Mahfudz (البصيرة: مجلة الدراسات الإسلامية, 2025)
This study aims to examine the existence and influence of mutawātir readings (qirā’āt) on the determination of legal rulings in Rawā’i‘ al-Bayān fī Tafsīr Āyāt al-Aḥkām min al-Qur’ān authored by Muḥammad ‘Alī al-Ṣābūnī. The research focuses on five selected legal verses that contain qirā’āt variations, namely the words: nansa-hā, yuṭīqūnahu, yaṭhurna, qur’, and arjulakum. It addresses how these mutawātir readings contribute to the formulation of legal conclusions within al-Ṣābūnī’s exegesis. The study employs a qualitative approach, using the comparative exegesis method (al-tafsīr al-muqāran) and a thematic approach to legal verses containing mutawātir readings. The primary sources consist of two volumes of Rawā’i‘ al-Bayān, while the secondary sources include classical and contemporary works relevant to the sciences of qirā’āt and legal exegesis. Documentation and textual analysis methods were applied to uncover the structure of al-Ṣābūnī’s exegesis and the role of qirā’āt in his legal reasoning. The findings show that mutawātir readings play a significant role in enriching the semantic scope of Qur’anic terms and in shaping legal understanding, although they are not always the principal basis for legal preference (tarjīḥ). Al-Ṣābūnī tends to combine the method of exegesis by transmission (bi al-ma’thūr) and exegesis by opinion (bi al-ra’y), with strong reliance on juristic opinions and consideration of the objectives of Islamic law (maqāṣid al-sharī‘ah). In certain cases such as abrogation (naskh) and the waiting period (‘iddah) differences in readings had a direct impact on the legal conclusion. In other cases such as the rulings on ablution (wuḍū’) and menstruation  mutawātir readings served more as a support for semantic breadth rather than as determinants for legal preference. The study concludes that understanding mutawātir readings is essential for the development of Qur’anic legal interpretation in the contemporary era, as these readings are a fundamental tool in constructing legal reasoning within tafsīr. Therefore, the employment of qirā’āt in exegesis as exemplified by al-Ṣābūnī constitutes a significant scholarly contribution to the methodology of deriving rulings from the Qur’an.